PENGARUH TINGKAT PROFITABILITAS, LEVERAGE, DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING (Studi pada Industri Barang Konsumsi Makanan & Minuman Yang Terdaftar Di BEI Periode 2015 -2019) - Christina Dewi Wulandari; Tri Damayanti; Apriana Anggreini Bangun; Aulia Rizki Anggraini (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The manufacturing industry sector is the main focus of economic growth in Indonesia, the decline in the value of companies in the economic growth sector of the manufacturing industry will have a major effect on the economy in Indonesia, therefore companies are required to increase the value of the company in order to attract investors. This study was conducted to analyze the effect of profitability , Leverage, and debt policy on firm value with dividend policy as the Intervening variable. The object of this research is a manufacturing company in the consumer goods industry sector by using non-probability sampling (non-random sampling) and purposive sampling methods. The analysis technique used is multiple linear regression and path analysis. Based on the results of the study, it was found that probability, leverage had no effect on dividend policy. Meanwhile, debt policy has an effect on dividend policy. Leverage, debt policy has no effect on firm value. While the level of profitability affects the value of the company. dividend policy has no effect on firm value. Dividend policy cannot mediate leverage and debt policy on firm value. Meanwhile, dividend policy can mediate the relationship between the level of profitability and firm value.